Influence of clinical history on MRI interpretation of optic neuropathy. Issue 9 (September 2016) - Bansal, Neil K.; Hagiwara, Mari; Borja, Maria J.; Babb, James; Patel, Sohil H.
Abstract: Background and purpose: Clinical history is known to influence interpretation of a wide range of radiologic examinations. We sought to evaluate the influence of the clinical history on MRI interpretation of optic neuropathy. Materials and methods: 107 consecutive orbital MRI scans were retrospectively reviewed by three neuroradiologists. The readers independently evaluated the coronal STIR sequence for optic nerve hyperintensity and/or atrophy (yes/no) and the coronal post-contrast T1WI for optic nerve enhancement (yes/no). Readers initially evaluated the cases blinded to the clinical history. Following a two week washout period, readers again evaluated the cases with the clinical history provided. Inter-reader and reader-clinical radiologist agreement was assessed using Cohen's simple kappa coefficient. Results: Intra-reader agreement, without and with provision of clinical history, was 0.564–0.716 on STIR and 0.270–0.495 on post-contrast T1WI. Inter-reader agreement was overall fair-moderate. On post-contrast T1WI, inter-reader agreement was significantly higher when the clinical history was provided (p = 0.001). Reader-clinical radiologist agreement improved with provision of the clinical history to the readers on both the STIR and post-contrast T1WI sequences. Conclusions: In the MRI assessment of optic neuropathy, only modest levels of inter-reader agreement were achieved, even after provision of clinical history. Provision of clinical history improved inter-reader agreement, especially when assessing for optic nerve enhancement. These findings confirm the subjective nature of orbital MRI interpretation in cases of optic neuropathy, and point to the importance of an accurate clinical history. Of note, the accuracy of orbital MRI in the context of optic neuropathy was not assessed, and would require further investigation.